1976
DOI: 10.1192/bjp.128.1.57
|View full text |Cite
|
Sign up to set email alerts
|

Some Personality Characteristics of Patients with Anorexia Nervosa

Abstract: Twenty-two female patients with anorexia nervosa were assessed by means of objective personality testing. The EPI, Leyton Obsessional Inventory, Cattell's 16 PF and Raven's Matrices were used for this purpose. The personality profile that emerged was of a highly neurotic and introverted person with moderately severe obsessional features and average intelligence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
2

Year Published

1980
1980
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 9 publications
2
41
2
Order By: Relevance
“…These symptoms, however, also tend to be related to issues of power and control, and therefore may be a characterological aspect of the anorexic (Roth & Golloway, 1984). Smart et al, (1976) found that anorexic patients reported more obsessional symptoms, traits, and related distress than normal subjects.…”
Section: It Is Interesting To Note That the Increase Inmentioning
confidence: 91%
See 4 more Smart Citations
“…These symptoms, however, also tend to be related to issues of power and control, and therefore may be a characterological aspect of the anorexic (Roth & Golloway, 1984). Smart et al, (1976) found that anorexic patients reported more obsessional symptoms, traits, and related distress than normal subjects.…”
Section: It Is Interesting To Note That the Increase Inmentioning
confidence: 91%
“…The imperfections of the bulimic (e.g., perceived size) (Ben-Tovim, Marilov, & Crisp, 1979;Crisp & Bhat, 1982;Smart, Beaumont, & George, 1976;Stonehill & Crisp, 1977).…”
Section: It Is Interesting To Note That the Increase Inmentioning
confidence: 99%
See 3 more Smart Citations